Chiang Yee and his circle : Chinese artistic and intellectual life in Britain, 1930-1950 - Bevan, Paul, Ph. D.; Witchard, Anne Veronica; Zheng, Da, 1953- (Hong Kong University Press, 2022)
Celebrates the life and work of Chiang Yee (1903-1977), a Chinese writer, poet, and painter who made his home in London, England during the 1930s and 1940s. It examines Chiang's relationship with his circle of friends and colleagues in the English capital, and assesses the work he produced during his sojourn there. This edited volume, with contributions from eleven distinguished scholars, tells a story of a Chinese intellectual community in London that up to now has been largely overlooked.